Pengembangan Bukit Cemara Menuju Wisata Ramah Melalui Community Based Tourism di Kabupaten Karangasem - Susanti, Putu Herny; Wilyadewi, Ida I Dewa Ayu Yayati; Oktarini, Luh Nik; Purnami, Ni Luh Tia Ayu (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
The Covid-19 pandemic has had an impact on the tourism industry in Indonesia and the world. After the pandemic has recovered, all sectors of the tourism industry in the world have adapted to the new normal life, including the Bukit Cemara tourist destination in Karangasem Regency. This study aims to examine the development strategy of Bukit Cemara tourism attraction in Karangasem Regency towards friendly attraction in order that the number of tourist visits can increase significantly. This study uses a qualitative research method based on literature review, observation and interviews with the support of the Interpretive Structural Modeling (ISM) analysis tool. This study concludes that tourism management in Bukit Cemara has not been maximized. Therefore, a development strategy is needed that includes the role of several elements to become friendly tourism. Among them are the needs for the role of traditional villages and local society, the maximum role of local governments, improvement of aware of tourism work, active involvement of academics related to human resource development in developing friendly tourism.